منهج القرآن في إعمال العقل من خلال سورة البقرة: دراسة تحليلية - مصطفى،علي عبد القادر (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
This research aims to examine the methodology that can be deduced from the Noble Qur'an in utilizing the mental faculty through one of its chapters, Surat al-Baqara (Chapter of the Cow). The study is analytical; it addresses the definitions of reason by various mutakallimin (advocates of Islamic scholastic theology trend), philisophers and Usuli scholars (scholars of principles of jurisprudence) whilst indicating differences among them. At a later stage, it exposes the terms synonymous to 'reason' in the Qur'an, comparing the broad meaning of reason post Islam and the Islamic reason; it shows how the Islamic reason revolutionizes corrupt concepts and deviant views that precede it. The discussion goes upon to touch on the controversy of divergence between religion (religious texts) and reason; the researcher proves the controversy to be mere illusion and that there is no divergence between authentic religious texts and sound reason. Then, the researcher addresses the singularity of the Qur'anic deductions and intellectual approaches by which the Noble Book puts forward its evidence on issues directed equally to Muslims and non-Muslims. Later, the study reveals the many virtues of Surat al-Baqara in addition to exposing certain Islamic legal rules, the blessed Surat holds, to disclose its merit and intents within. The conclusion culminates with the most important section of the research; the discussion evolved around the Qur'anic parameters required in using reason in Surat al-Baqara. The findings of the study uncover five parameters considered the most important in this blessed Surat if implemented by Muslims as well as non Muslims. In addition to other parameters evidenced in different chapters of the Noble Quran, they would be the ultimate drive to creating a reason close to infallibility. The researcher limits these parameters in Surat al-Baqara to realist, critical, comparative, objective, impartial, controversy-free, curiosity and inquisition. Inductive and analytical approaches were adopted in this study.